Vietnamese-Taiwanese Multicultural Families in Ho Chi Minh City, Vietnam: A Comparative Analysis - Phan Thi Hong Xuan; Ho – Hsien Chen; Vo Phan My Tra (Migration Letters, 2023)
Vietnam has gained recognition as a nation wherein a substantial influx of married women have migrated to Taiwan during the 1990s. Nevertheless, empirical evidence indicates that there is currently a growing inclination among Vietnamese-Taiwanese couples to reside in Ho Chi Minh City, Vietnam. Employing the approach of cultural variables and rational choice, This study presents findings from 33 interviews conducted with multicultural families, encompassing the life stories of 12 women, 10 husbands, and 11 children, to take into account various aspects within family dynamics, as well as considerations of nationality and citizenship. The findings indicate that multicultural households in Ho Chi Minh City predominantly originate from voluntary decisions, driven by love and a desire for harmonious cohabitation, and exhibit a strong sense of empathy, harmony, and adaptability in terms of linguistic and cultural practices within their domestic activities. Children born into legally recognized multicultural households often have the opportunity to acquire dual citizenship; however, the level of understanding of citizenship rights varies depending on the specific circumstances and context surrounding each instance. Foreign spouses of Vietnamese citizens residing in Vietnam encounter some disadvantages, sometimes facing pertaining to their residency entitlements.